2022
DOI: 10.1073/pnas.2109226119
|View full text |Cite
|
Sign up to set email alerts
|

Social disadvantage, economic inequality, and life expectancy in nine Indian states

Abstract: Significance India is one of the most hierarchical societies in the world. Because vital statistics are incomplete, mortality disparities are not quantified. Using survey data on more than 20 million individuals from nine Indian states representing about half of India’s population, we estimate and decompose life expectancy differences between higher-caste Hindus, comprising other backward classes and high castes, and three marginalized social groups: Adivasis (indigenous peoples), Dalits (oppressed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…31 Hence, there is every possibility that COVID-19 deaths are underreported out of proportion among those with the slightest chance of getting tested, getting timely treatment, and, if expired, the most chance of not getting reported. 32,33…”
Section: Discussionmentioning
confidence: 99%
“…31 Hence, there is every possibility that COVID-19 deaths are underreported out of proportion among those with the slightest chance of getting tested, getting timely treatment, and, if expired, the most chance of not getting reported. 32,33…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our study has revealed a significantly lower mortality risk among older adults belonging to the General and OBC caste compared to SC/ST caste but a higher mortality risk among Muslims than Hindus. Though SC/ST and Muslims are considered as marginalized social groups in India and they are socio-economically poorer (Desai, 2010;Thorat & Newman, 2010;Vyas et al, 2022), they also have lower life expectancies (Kumari & Mohanty, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…India is one of the world's most hierarchical societies where health and social disadvantage are inextricably connected (Vyas et al, 2022). However, in today's India, concerns about the mortality and health of India's underprivileged social groups are still pressing and recent studies have highlighted that SC & ST have much shorter life expectancies than the upper caste (general caste) and these enormous differences have lasted nearly for two decades, from…”
Section: Discussionmentioning
confidence: 99%
“…1997 to 2016 (Gupta & Sudharsanan, 2022;Vyas et al, 2022). They have also indicated that mortality disparities in India are not just a childhood phenomenon, but are also increasing more and more problems among older populations too (Gupta & Sudharsanan, 2022).…”
Section: Discussionmentioning
confidence: 99%